THE ENORMITY OF LITERARY ANALYSIS TO TEACHING AMERICAN LITERATURE - Didik Murwantono (Dinamika Bahasa dan Budaya, 2010)
Some indispensable factors influencing in students’ motivation are such as their interest in and enthusiasm for the material used in the class and the level of their persistence with the learning tasks. Those factors are going to applied in American Literature class through some literary analysis. Literary analysis invites students to the ongoing debate about the place of the theory and practice in the literature classroom. This article helps students develop and articulate their interpretations from a variety of theoretical approaches by equipping them with the critical tools for reading. The writer only highlights four literary analysis on American literature in views of  poems and prose. These primary texts include Joseph Bruchac’s poem “The Circle of Thanks”, Thomas King’s “Border”, Waldo Emerson’s “Self-Reliance, and Whitman’s “Crossing Brooklin Ferry”. Not all theories but some are discussed in details in this article. As a final point, these types of involvement are something that can not be imposed; it must come from the materials and courses that are implemented in the classroom.   Keywords: Literary analysis, criticism, interpretation, American literature, theory and practice